Phragmites stimulation and natural attenuation of indigenous microbial community accelerated bioremediation of oil contaminated soil. (18th April 2019) - Yu, Wenhe; Song, Jiayu; Chen, Changzhao; Song, Quanwei; Zhao, Chaocheng; Li, Xingchun; Chen, Hongkun
Abstract: Illumina high-throughput sequencing method was used to reflect fluctuation of indigenous microbial community during phragmites stimulation process in this study. Results showed Proteobacteria, Fimicutes, and Actinobacteria were most influential in process, Firmicutes and Deinococcus-Thermus were positively affected by nutrient amendment. Firmicutes can be seen as indicator of degradation rate. Dietzia, Salinimicrobium, and Halomonas were the most dominant genus in both Phragmites and Blank setups. These results indicated phragmites addition improved the efficiency of biodegradation and significantly regulated the microbial community structure and functions during remediation process.